2021
DOI: 10.29026/oea.2021.200030
|View full text |Cite
|
Sign up to set email alerts
|

High-<i>Q</i> resonances governed by the quasi-bound states in the continuum in all-dielectric metasurfaces

Abstract: The realization of high-Q resonances in a silicon metasurface with various broken-symmetry blocks is reported. Theoretical analysis reveals that the sharp resonances in the metasurfaces originate from symmetry-protected bound in the continuum (BIC) and the magnetic dipole dominates these peculiar states. A smaller size of the defect in the broken-symmetry block gives rise to the resonance with a larger Q factor. Importantly, this relationship can be tuned by changing the structural parameter, resulting from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 89 publications
(38 citation statements)
references
References 56 publications
1
37
0
Order By: Relevance
“…[ 37–40 ] A periodic array of nanocubes without air‐slots can achieve the symmetry‐protected BIC. [ 41 ] This mode can stably exist above the lightline with infinite Q factor, as verified by the band structure calculation shown in the Supporting Information. Once the broken symmetry is introduced, the mode turns into a leaky mode with high Q factor.…”
Section: Structure Design and Theoretical Analysismentioning
confidence: 57%
See 1 more Smart Citation
“…[ 37–40 ] A periodic array of nanocubes without air‐slots can achieve the symmetry‐protected BIC. [ 41 ] This mode can stably exist above the lightline with infinite Q factor, as verified by the band structure calculation shown in the Supporting Information. Once the broken symmetry is introduced, the mode turns into a leaky mode with high Q factor.…”
Section: Structure Design and Theoretical Analysismentioning
confidence: 57%
“…Like the perturbation of the symmetry-protected BIC, [39], [40] the dimension of the air-slot would determine the Q factor of the BIC, which consequently modifies the enhanced electric field over the sidewall surface of the air-slot as well as the SHG process. In Figure 2d, we plot the enhancement factors of the electric field and the SHG as functions of the air-slot width a with respect to the values obtained with a=0 nm, i.e., nanocubes without air-slots.…”
Section: Structure Design and Theoretical Analysismentioning
confidence: 99%
“…Mie resonators are highly multi-mode open cavities. Their eigenmodes, being non strictly orthogonal within the resonator volume 120 , can either interfere giving rise to Fano resonances 13,15 or strongly couple to each other, originating Friedrich-Wintgen BICs 21,22 . Exploiting this approach, Koshelev et al 68 reported an experimental record quality factor in an isolated AlGaAs resonator with a maximum SHG efficiency .…”
Section: Collective Resonances In Nonlinear Metasurfacesmentioning
confidence: 99%
“…21−24 for details]. In contrast to the embedded eigenstates or bound state in the continuum which cannot be accessed by the excitation in the continuum 25 , the so-called electromagnetic anapole condition provides a nonscattering condition sustained under the excitation of external field 5,26 , which resembles a promising physical mechanism for tailoring light-matter interaction in a nonscattering manner [21][22][23][24]27 . It is generally perceived that such an anapole condition requires that all of the in-duced electromagnetic multipole moments are suppressed at the same wavelength, resembling the canonical way of realizing the radiationless anapole condition 4−20 .…”
Section: Introductionmentioning
confidence: 99%